Alkaline arginine promotes the gentamicin-mediated killing of drug-resistant Salmonella by increasing NADH concentration and proton motive force - Zhu, Chunyang; Zhou, Yanhong; Kang, Jian; Yang, Heng; Lin, Jinglin; Fang, Binghu (Frontiers in Microbiology, 2023)
Antimicrobial resistance, especially the development of multidrug-resistant strains, is an urgent public health threat. Antibiotic adjuvants have been shown to improve the treatment of resistant bacterial infections. This study found that alkaline arginine significantly increased gentamicin, tobramycin, kanamycin, and apramycin-mediated killing of drug-resistant Salmonella, including multidrug-resistant strains. Mechanistic studies showed that exogenous arginine was shown to increase the proton motive force, increasing the uptake of gentamicin and ultimately inducing bacterial cell death. Furthermore, in mouse infection model, arginine effectively improved gentamicin activity against Salmonella typhimurium. These findings confirm that arginine is a highly effective and harmless aminoglycoside adjuvant and provide important evidence for its use in combination with antimicrobial agents to treat drug-resistant bacterial infections.